2018
DOI: 10.1016/j.celrep.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Targeting of PARP1 and RAD52 Triggers Dual Synthetic Lethality in BRCA-Deficient Tumor Cells

Abstract: SUMMARY PARP inhibitors (PARPis) have been used to induce synthetic lethality in BRCA-deficient tumors in clinical trials with limited success. We hypothesized that RAD52-mediated DNA repair remains active in PARPi-treated BRCA-deficient tumor cells and that targeting RAD52 should enhance the synthetic lethal effect of PARPi. We show that RAD52 inhibitors (RAD52is) attenuated single-strand annealing (SSA) and residual homologous recombination (HR) in BRCA-deficient cells. Simultaneous targeting of PARP1 and RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…Thus, in tumors in which BRCA2 is active, inhibition of RAD52 could be a valuable strategy to exploit PARPi. Although it has been recently reported that PARPi and RAD52 deficiency show a synergic effect on viability in BRCA2-deficient cells, inhibition of PARP or RAD52 has no consequences if BRCA2 is functional [127]. This result would suggest that loss of fork protection per se is not enough to give PARPi sensitivity, as suggested, or that also MUS81-dependent cleavage, which is absent if RAD52 is inhibited, must take place to confer PARPi sensitivity.…”
Section: Conclusion and Potential Implications Of Replication Fork-rmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, in tumors in which BRCA2 is active, inhibition of RAD52 could be a valuable strategy to exploit PARPi. Although it has been recently reported that PARPi and RAD52 deficiency show a synergic effect on viability in BRCA2-deficient cells, inhibition of PARP or RAD52 has no consequences if BRCA2 is functional [127]. This result would suggest that loss of fork protection per se is not enough to give PARPi sensitivity, as suggested, or that also MUS81-dependent cleavage, which is absent if RAD52 is inhibited, must take place to confer PARPi sensitivity.…”
Section: Conclusion and Potential Implications Of Replication Fork-rmentioning
confidence: 89%
“…While this situation parallels synthetic lethality between BRCA defects and inhibition of PARP1, the mechanisms of synthetic lethality are likely different and therefore inhibiting RAD52 may be beneficial in cases where PARP inhibitor resistance has emerged [125,126]. Moreover, it has been shown recently, that simultaneous inhibition of PARP1 and RAD52 can have a synergistic effect on the tumor cell killing [127]. It remains unclear, however, which of the many cellular functions of RAD52, which we discussed above, allow for survival and proliferation of BRCA-deficient cells and whether there are other circumstances when it would be beneficial to target RAD52.…”
Section: Conclusion and Potential Implications Of Replication Fork-rmentioning
confidence: 99%
“…In addition to PARP and DNA-PK inhibitors, ATR, CHK1, and WEE1 inhibitors are under development and being tested in current clinical trials alone or in combination with chemotherapy ( Brown et al, 2017 ). Furthermore, combinations of DNA repair inhibitors, such as with PARP and RAD52 combinations, are being developed based on exciting preclinical results ( Sullivan-Reed et al, 2018 ). In this study, we demonstrated that combining DNA-PK inhibition and PARP inhibition with IR in HNSCC results in further reduction in cell proliferation and clonogenic survival.…”
Section: Discussionmentioning
confidence: 99%
“…1 3 Interestingly, however, the inability of acute ATRi treatment to impair DNA end resection allows the engagement of RAD52-dependent pathways that mitigate the cytotoxic effect of PARP inhibitors and other drugs. Previous studies have shown that RAD52-mediated repair could compensate for loss of HR in cells lacking the PALB2-BRCA2 machinery and therefore, could represent a mechanism of resistance to acute treatments with PARP inhibitors and ATR inhibitors 52,54,55,62 . Notably, RAD52 was reported to foster RAD51-dependent recombination in brca2-deficient cells 52 , therefore bypassing the requirement of PALB2 phosphorylation by ATR and possibly explaining the residual levels of RAD51 foci observable after acute ATRi and PARPi.…”
Section: Long-term Atr Inhibition Bypasses Overexpression Of E2f1mentioning
confidence: 99%